2021
DOI: 10.1016/j.genrep.2021.101116
|View full text |Cite
|
Sign up to set email alerts
|

Expression signature of lncRNA APTR in clinicopathology of breast cancer: Its potential oncogenic function in dysregulation of ErbB signaling pathway

Abstract: A growing amount of evidence has revealed that long noncoding RNAs (lncRNAs) play significant roles in malignancies through different mechanisms especially the competing endogenous RNA (ceRNA). They have also been shown to have the potential diagnostic, prognostic and therapeutic biomarker capacity in oncology research. Recently, lncRNA Alu-mediated p21 transcriptional regulator (APTR) has been proposed as an oncogenic lncRNA in development and clinical outcome of some cancers. However, clinical and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Bioinformatic analysis identified ten miRNAs as putative APRT interactors, but miR-29 was not included [ 76 ]. APTR was demonstrated to repress CDKN1A transcription by binding to the promoter and recruiting the PRC2 complex [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic analysis identified ten miRNAs as putative APRT interactors, but miR-29 was not included [ 76 ]. APTR was demonstrated to repress CDKN1A transcription by binding to the promoter and recruiting the PRC2 complex [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…APTR was demonstrated to repress CDKN1A transcription by binding to the promoter and recruiting the PRC2 complex [ 77 ]. APTR was recently reported to be increased in breast tumors compared to normal adjacent breast tissue and to be higher in larger tumors, suggesting an oncogenic function [ 76 ]. Another recent study reported that APTR directly interacts with ERα in Ht-UtLM human leiomyoma cells [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…LncRNA Alu-mediated p21 transcriptional regulator (APTR), which suppresses the CDKN1A/p21 promoter, was found to regulate cell proliferation in several cancers, such as human glioma [9] , osteosarcoma [10] , breast cancer [11] , thyroid cancer [12] and hepatic stellate cells [13] . In this study, we investigated lncRNA APTR's role in GC, which was lower expressed in gastric tumor tissues than in gastric normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…These non‐coding RNAs interact with each other and orchestrate significant processes such as metastasis in cancer cells. 14 , 15 One of the functions of circRNAs is to sponge miRNAs, which in turn affects the expression of their target mRNAs. 16 Such interactions have been investigated in the context of competing endogenous RNA (ceRNA) regulatory networks in BC.…”
Section: Introductionmentioning
confidence: 99%